Collection of dried fish in a basket - Mumbai Archive Project Team (Jio Institute, 2024)
The simplest method of drying is sun drying, which is suitable considering Mumbai’s hot climate. After leaving the fish in the sun for several days, the heat and airflow gradually remove moisture. Once they are sufficiently dry, the fish are collected in baskets.